Hubungan Faktor Teman Sebaya, Iklan Rokok, Lingkungan Keluarga, dan Stres dengan Kebiasaan Merokok Siswa SMA di Kabupaten Pangkep - Erlani Erlani; Juherah Juherah; Nurhaidah Nurhaidah; Nur Nadwah Ilahi (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2026)
The 2019 Global Youth Tobacco Survey (GYTS) data shows an increasing trend in smoking prevalence among adolescents aged 13–15 years, from 18.3% in 2016 to 19.2% in 2019. This phenomenon is confirmed by the results of the 2023 Indonesian Health Survey (SKI) which places the 15–19 age group as the largest proportion of smokers with a percentage reaching 56.5%, followed by the 10–14 age group at 18.4%. Smoking has become a necessity that is difficult to avoid for some people due to the addictive effects it causes. Although this habit is considered to provide recreational or enjoyable effects for the perpetrator, smoking activity in reality has a negative impact, both on the health of active smokers and passive smokers around them. The purpose of this study is to determine the relationship between peer factors, cigarette advertising, family environment, and stress with smoking habits of high school students in Pangkep Regency. This study is an observational analytical study with a cross-sectional study approach. The main population of this study was 64 male students at SMA Muhalmadiyah Pangkep and 179 female students at SMA Negeri 20 Pangkep. The sample size was 184 out of 243 students. The sampling technique used purposive sampling, which included male students in grades 10 to 12, students who smoked and non-smoked, and students who were ready to be respondents/interviewed. The instrument used for data collection was a questionnaire that had been validated by other researchers. The results showed that the cigarette advertisement factor (p-value  = 0.811 > 0.05) was not significantly related, while the peer factor (p-value  = 0.013 < 0.05), the family environment factor (p-value  = 0.025 < 0.05), and the internal stress factor (p-value  0.010 < 0.05) were related to the smoking habit of students at SMA Kabupaten Pangkep. The conclusion of this study was that there was no correlation between cigarette advertisements and smoking habit, but the peer factor, family environment, and stress were related to smoking habit.